2021
DOI: 10.3390/en15010149
|View full text |Cite
|
Sign up to set email alerts
|

Fouling Mitigation of Ion Exchange Membranes in Energy Conversion Devices

Abstract: In this study, three different environmentally friendly fouling mitigation technologies are suggested and are investigated in reverse electrodialysis (RED) to develop the most appropriate fouling mitigation technology for RED: applying direct current, flowing a solution with high salt concentration, and periodically switching river and seawater streams in RED. The quantitative level of anion exchange membrane fouling mitigation is evaluated in terms of the power density and the amount of power generation of RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Figure 5 shows the variation of electrical resistance of the four different IEMs immersed in 0.1 wt.% foulant + 0.017 M NaCl solutions. The foulants were introduced only in river water (0.017 M NaCl) to foul the IEMs effectively since the previous studies have reported the mitigation behavior of IEMs’ fouling in a NaCl solution of high concentration such as seawater (0.513 M NaCl) [ 18 , 19 ]. As shown in Figure 5 a,b,e,f, the anionic foulant, SDBS_348_AS, causes only the AEMs to increase electrical resistance and the cationic foulant, CC_340_CS, results in an increase in electrical resistance only for the CEMs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 5 shows the variation of electrical resistance of the four different IEMs immersed in 0.1 wt.% foulant + 0.017 M NaCl solutions. The foulants were introduced only in river water (0.017 M NaCl) to foul the IEMs effectively since the previous studies have reported the mitigation behavior of IEMs’ fouling in a NaCl solution of high concentration such as seawater (0.513 M NaCl) [ 18 , 19 ]. As shown in Figure 5 a,b,e,f, the anionic foulant, SDBS_348_AS, causes only the AEMs to increase electrical resistance and the cationic foulant, CC_340_CS, results in an increase in electrical resistance only for the CEMs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the fouling mitigation of the IEMs with different surface properties used in this study was investigated. The previous studies reported that the high concentration of a NaCl solution such as seawater effectively mitigated the membrane fouling formed by electrostatic attraction between ionic foulants and IEMs [ 18 , 19 ]. Thus, the flowing of a concentrated NaCl solution into a dialysate and a concentrate between RED operations was used as a fouling mitigation method in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations